2022
DOI: 10.1038/s41467-022-29374-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrically driven reprogrammable phase-change metasurface reaching 80% efficiency

Abstract: Phase-change materials (PCMs) offer a compelling platform for active metaoptics, owing to their large index contrast and fast yet stable phase transition attributes. Despite recent advances in phase-change metasurfaces, a fully integrable solution that combines pronounced tuning measures, i.e., efficiency, dynamic range, speed, and power consumption, is still elusive. Here, we demonstrate an in situ electrically driven tunable metasurface by harnessing the full potential of a PCM alloy, Ge2Sb2Te5 (GST), to rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(105 citation statements)
references
References 43 publications
0
105
0
Order By: Relevance
“…The structure demonstrated here provides the first truly wideband-tunable THG devices and paves the way for the design of nonlinear optical structures with improved efficiency and functionality for a wide range of applications, such as a combined band-and-phase modulation for THG microscopy. These structures can be combined with ultrafast and compact heating processes using indium tin oxide (ITO) Joule heaters, as demonstrated in other studies, [33][34][35] to form a new platform for electrically tunable chip-scale nonlinear optical devices. The structure here can also be a reliable platform for wideband tuning of THG with higher conversion efficiencies: 1) at the longer infrared wavelengths where the GST optical loss is minimal or 2) using alloys of GST, for example, Ge 2 Sb 2 Se 4 Te 1 (in short, GSST), [36,37] which provide less optical loss at the 1100-1600 nm wavelength range.…”
Section: Discussionmentioning
confidence: 99%
“…The structure demonstrated here provides the first truly wideband-tunable THG devices and paves the way for the design of nonlinear optical structures with improved efficiency and functionality for a wide range of applications, such as a combined band-and-phase modulation for THG microscopy. These structures can be combined with ultrafast and compact heating processes using indium tin oxide (ITO) Joule heaters, as demonstrated in other studies, [33][34][35] to form a new platform for electrically tunable chip-scale nonlinear optical devices. The structure here can also be a reliable platform for wideband tuning of THG with higher conversion efficiencies: 1) at the longer infrared wavelengths where the GST optical loss is minimal or 2) using alloys of GST, for example, Ge 2 Sb 2 Se 4 Te 1 (in short, GSST), [36,37] which provide less optical loss at the 1100-1600 nm wavelength range.…”
Section: Discussionmentioning
confidence: 99%
“…If the temperature continues to rise, the regular crystals inside the cGST slowly turn into disordered nuclei again, and the cGST returns to aGST after undergoing rapid annealing at 640 • C (913.15 K) [57]. The whole reversible phase change process is continuously related to the heating temperature and heating time, and this process and the temperature profile for the reversible phase change operation can be described in various experimental ways [58][59][60][61]. For example, the electrical pulsing schemes and meta-atom temperature profiles are shown by designing an electrothermal metasurface switching [58], and the corresponding temperature responses can be obtained when the GST is heated by a resistive microheater integrated with a phase-change metasurface [59].…”
Section: Methodsmentioning
confidence: 99%
“…The whole reversible phase change process is continuously related to the heating temperature and heating time, and this process and the temperature profile for the reversible phase change operation can be described in various experimental ways [58][59][60][61]. For example, the electrical pulsing schemes and meta-atom temperature profiles are shown by designing an electrothermal metasurface switching [58], and the corresponding temperature responses can be obtained when the GST is heated by a resistive microheater integrated with a phase-change metasurface [59]. Since GST is non-volatile, once the phase transition is completed, it can maintain the corresponding state at room temperature for a long time, so our research was carried out at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Active tuning of amplitude, phase or polarization is achieved either by modifying the optical properties of these meta-atoms or those of their surroundings 23 , 24 . Recent studies have demonstrated the use of phase change materials 25 31 , transparent conducting oxides 9 , 32 34 , two-dimensional materials 35 39 , semiconductors 40 42 and liquid crystals 10 , 43 47 as tuning media, with very few examples achieving individual pixel control 9 , 10 , 34 . Moreover, using the concept of Huygens’ metasurfaces, it is possible to limit the coupling between amplitude and phase modulation 10 , 48 , 49 .…”
Section: Introductionmentioning
confidence: 99%